Adherence to the EAU guideline recommendations for systemic chemotherapy in penile cancer: results of the E-PROPS study group survey - Distler, Florian A.; Pahernik, S.; Gakis, G.; Hutterer, G.; Lebentrau, S.; Rink, M.; Nuhn, Philipp; Brookman-May, S.; Burger, M.; Gratzke, C.; Wolff, I.; May, M. (World journal of urology, 2020)
To validate the adherence of urologists to chemotherapy recommendations given in the EAU guidelines on PeCa. The European Association of Urology (EAU) guidelines on penile cancer (PeCa) are predominantly based on retrospective studies with low level of evidence.